Biotechnology and nanotechnology : science-based enabling technologies as windows of opportunity for LDCs? - Niosi, Jorge (2007)
Examines biotechnology and nanotechnology in order to assess whether these emerging technologies do indeed offer windows of opportunity for LDCs to catch up, and if so, which strategies enable successful involvement.